Optimizing Job Satisfaction - Wardana, Fandi; Isa Indrawan, Muhammad (PT. Multidisciplinary Press Indonesia, 2024)
This research aims to examine the influence of work motivation and discipline on job satisfaction with compensation as an intervening variable at the Bank Indonesia Pematangsiantar Representative Office. Humans (HR) are the most important factor in the growth and development of an organization or business. That in conditions of globalization, human quality in companies is always a source of competition. Companies that want to grow and develop well must organize their human resources intellectually, spiritually, creatively, morally and responsibly. The results of this research are as follows: Work Discipline has a positive and significant effect on Job Satisfaction with an original sample value of 0.267 and a p value of 0.048. Work Discipline has a positive and significant effect on compensation with an original sample value of 0.269 and a p value of 0.042. Compensation has a positive and significant effect on job satisfaction with an original sample value of 0.350 and a p value of 0.011. Motivation has a positive and significant effect on Job Satisfaction with an original sample value of 0.315 and a p value of 0.045. Motivation has a positive and significant effect on compensation with an original sample value of 0.624 and a p value of 0.000. Work Discipline has a positive and significant effect on Job Satisfaction through Compensation with an original sample value of 0.094 and a p value of 0.105. Motivation has a positive and significant effect on Job Satisfaction through Compensation with an original sample value of 0.218 and a p value of 0.014.